Bibliometric and visualised analysis on non-invasive cerebellar stimulation from 1995 to 2021 - He, Lin; Guo, Qi-Fan; Hu, Yu; Tan, Hui-Xin; Chen, Yi; Wang, Chen-Han; Zhou, Tian-Yu; Gao, Qiang (Frontiers in Neuroscience, 2023)
Background: The non-invasive cerebellar stimulation (NICS) is a neural modulation technique, which shows the therapeutic and diagnostic potentials for rehabilitating brain functions in neurological or psychiatric diseases. There is a rapid growth in the clinical research related to NICS in recent years. Hence, we applied a bibliometric approach to analyze the current status, the hot spots, and the trends of NICS visually and systematically. Methods: We searched the NICS publications from the Web of Science (Wos) between 1995 and 2021. Both VOSviewer (1.6.18) and Citespace (Version 6.1.2) software were used to generate the co-occurrence or co-cited network maps about the authors, institutions, countries, journals, and keywords. Results: A total of 710 articles were identified in accordance with our inclusion criteria. The linear regression analysis shows a statistical increase in the number of publications per year on NICS research over time (p<0.001). The Italy and University College London ranked the first in this field with 182 and 33 publications, respectively. Koch, Giacomo was the most prolific author (36 papers). The journal of Cerebellum, Brain stimulation and Clinical neurophysiology were the most three productive journals to publish NICS-related articles. Conclusion: Our findings provide the useful information regarding to the global trends and frontiers in NICS field. Hot topic was focused on the interaction between the transcranial direct current stimulation and functional connectivity in the brain. It could guide the future research and clinical application of NICS.